Status of Mangroves in Thekkumbad, Kannur, Kerala - K.M. Khaleel, P. Sreeja* and (Journal of Experimental Sciences, 2010)
The status of mangroves in Thekkumbad island of Kerala state was documented and assessed using the following parameters; total area covered, diversity, population structure and threats to mangroves. The study was conducted in Dec. 2008 using the plot quadrate method. Ten plots were non-randomly distributed in the study area. Eleven true mangrove species and six associates were found in the study area (Hâ€™=1.76). The dominant species were Rhizophora mucronata, Bruguiera cylindrica, Sonneratia alba and Excoecaria agallocha with important values 35.83, 32.43, 13.31, 25.02 respectively. Considering the small area of the island , the diversity was relatively high compared to nearby mangrove rich areas. However the continuous anthropogenic activities posses threat to the survival of mangroves. Thus the management of the present mangrove is urgent for a sustainable living. — Department of PG studies and Research in Botany, Sir Syed College, Taliparamba, Kerala â€“ 670142, India — Please Cite This Article As: P. Sreeja and K.M. Khaleel. 2010. Status of Mangroves in Thekkumbad, Kannur, Kerala. J. Exp. Sci. 1(8):1-2.